Study of Echocardiographic Measurements to Estimate the Physiological Cardiac Efficiency in Apparently Healthy Patients Visiting University Hospital for Cardiac Evaluation - Nepal, O.; Humagain, S.; Koju, R. P. (Kathmandu University Medical Journal, 2021)
Background Healthy cardiac function is evaluated by echocardiography in the non-invasive cardiology department. Cardiac functional and structural evaluation is assessed by cardiologists based on a physiologically defined normal range. We want to compute the physiological value of variables in the healthy population. Objective To compute and compare the recorded echocardiographic parameters among apparently healthy patients. Method This is a retrospective study and a total of 544 subjects whose standard reference range was within the normal limit are included for computational study. 268 males (52.8%) and 240 females (47.2%) were studied for the size of the aortic root, size of the left atrium, left ventricular internal diameter during diastole (LVIDd) and systole (LVIDs), interventricular septum during diastole and systole (IVSd and IVSs), left ventricular posterior wall during diastole (LVPWd) and systole (LVPWs) and ejection fraction (EF). Result Ejection fraction (EF) is not significantly different (p=0.14) between genders, Mean±SD; 70.45±6.7 for females and Mean±SD; 68.34±7.18 for males. The mean age of examined female patients is Mean±SD; 36.88±12.6 which is not significantly different with male patients age Mean±SD; 38.28±12.5. Males have larger left ventricular internal diameter in diastole, Mean±SD; 43.90±6.4 than females Mean±SD; 41.37±8.08. Ejection fraction for females is Mean±SD; 70.45±6.7, for males is Mean±SD; 68.34±7.18 with p=0.14. Conclusion Absolute echocardiographic measurements vary physiologically between apparently healthy genders yet the ejection fraction is not significantly different between both the genders in the examined Nepali population.